Quantification and antioxidant and anti-HCV activities of the constituents from the inflorescences of Scabiosa comosa and S. tschilliensis. Issue 5 (3rd March 2016) - Ma, J.N.; Bolraa, S.; Ji, M.; He, Q.Q.; Ma, C.M.
Abstract : To investigate the bioactive constituents of the inflorescences of Scabiosa comosa and S. tschilliensis, which are used traditionally for liver diseases, we tested the antioxidant activity using 2, 2′-diphenyl-1-picrylhydrazyl (DPPH), 2, 2′-azinobis-(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS), ferric reducing antioxidant potential (FRAP), and DPPH-ultra high performance liquid chromatography-mass spectrometer (UPLC-MS) assay. In addition, cell-based anti-HCV activity of the major compounds were evaluated. The plant extracts showed strong antioxidant activity. For the first time, 3, 4-dicaffeoylquinic acid (DCQA), 3, 5-DCQA and 4, 5-DCQA were identified from genus Scabiosa . A UPLC-MS method in multiple reaction monitoring (MRM) mode was established to quantify 18 constituents in the inflorescences of Scabiosa. The 3, 5-DCQA, chlorogenic acid and some glycosides of luteolin or apigenin were found to be the most abundant constituents. Chlorogenic acid and 3, 5-DCQA showed excellent radical scavenging activity and demonstrated anti-HCV activity. These findings provided scientific evidences for the clinic use of this herbal medicine for liver diseases. Abstract :